Health safety of dietary supplements. New legal regulations after government control of the agency NIK - Agnieszka Joanna Kowalska-Olczyk (Polish Pharmaceutical Society, 2023)
Subject of study The paper presents the proposed legal regulations regarding the safety of dietary supplements marketed in the territory of the Republic of Poland. Many of the proposed changes are in line with the European Union law, which treats dietary supplements as foodstuffs and nutritional substances. Purpose of research The aim of this paper was to analyze the results of the the NIK audit concerning the marketing of dietary supplements in the context of legal regulations in force in Poland and worldwide, postulated legislative improvements and literature on the subject. Material and methods The analysis of the proposed legal changes in the area of ​​dietary supplements marketed in the territory of the Republic of Poland was based on a public report of the government control agency of the Supreme Audit Office. Report "Introduction of dietary supplements to the market" was a continuation of the earlier report "Admission to marketing of dietary supplements", which analyzed the legal principles related to the marketing of these products. In connection with the irregularities revealed during the first inspection, the Supreme Audit Office recommended the implementation of legislative improvements in the area of ​​supervision over the marketing of dietary supplements. Results The NIK audit showed that the proper level of safety of dietary supplements was not ensured, which may be a real threat to the health of their users. State authorities responsible for monitoring the safety of such products performed their tasks unreliably. Supervision over the health quality of products placed on the market, as well as nutritional education related to their operation, were ineffective. Irregularities resulted from inadequate legislative solutions in the field of placing dietary supplements on the market for the first time and in the field of advertising these products. The need to undertake targeted legislative actions aimed at introducing new comprehensive legal solutions in the area of ​​safety of dietary supplements was indicated. Due to the fact that dietary supplements are widely available and purchased by consumers without a prescription in pharmacies, pharmacy outlets and online pharmacies, the results of the Supreme Audit Office audit are important for the pharmaceutical community. The role of the pharmacist is among others advising the patient on the choice of a dietary supplement appropriate for his age, sex and health condition and providing reliable information about possible interactions, contraindications to use or the method of taking this product. Before dispensing the product, the pharmacist should make sure for whom it is purchased and whether the patient knows what he is buying and how he should use the purchased preparation. Considering such wide competences of a pharmacist, knowledge about the safety of recommended products is an element of professionalism and responsibility for the life and health of consumers. Conclusions The aim of the introduced legal regulations should be to ensure a safe and transparent market for dietary supplements for the consumer. The above is to be achieved both through adequate legal changes in the above-mentioned area, as well as due to high fines for violating applicable laws. Key words: dietary supplements, control, safety, NIK report